2019
DOI: 10.1016/j.electstud.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Moderation or radicalisation? How executive power affects right-wing populists’ satisfaction with democracy

Abstract: Moderation or radicalisation? How executive power affects right-wing populists' satisfaction with democracy This paper investigates if access to executive power strengthens or weakens the positive relationship found in previous research between dissatisfaction with democracy and electoral support for the populist right. Research on political trust and satisfaction with democracy thus far has almost exclusively focused on cases in which the populist right has been excluded from governing coalitions. Will access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…With previous contributions already finding a negative relationship between populism and political trust-voters of populist parties tend to be less trusting of the political system (Dahlberg & Linde, 2017;Söderlund & Kestilä-Kekkonen, 2009) and low levels of political trust tend to further voting for populist parties (Doyle, 2011;Hooghe, Marien, & Pauwels, 2011;Rooduijn, 2018;Werts, Scheepers, & Lubbers, 2012)-the recent rise of populism does not bode well for Europe's democracies. Yet, others have pointed out the potentially healing effect of populism: With new parties that challenge the establishment entering the political stage, citizens formerly disappointed by and disenchanted with politics may reconcile with the democratic system (Haugsgjerd, 2019;Mudde & Rovira Kaltwasser, 2012). This seems particularly likely in democracies which leave a lot to be desired in the eyes of citizens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With previous contributions already finding a negative relationship between populism and political trust-voters of populist parties tend to be less trusting of the political system (Dahlberg & Linde, 2017;Söderlund & Kestilä-Kekkonen, 2009) and low levels of political trust tend to further voting for populist parties (Doyle, 2011;Hooghe, Marien, & Pauwels, 2011;Rooduijn, 2018;Werts, Scheepers, & Lubbers, 2012)-the recent rise of populism does not bode well for Europe's democracies. Yet, others have pointed out the potentially healing effect of populism: With new parties that challenge the establishment entering the political stage, citizens formerly disappointed by and disenchanted with politics may reconcile with the democratic system (Haugsgjerd, 2019;Mudde & Rovira Kaltwasser, 2012). This seems particularly likely in democracies which leave a lot to be desired in the eyes of citizens.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the majority of them have focused on the impact populist parties have on actual policies and the quality of democracy, disregarding any effects on the attitudes of ordinary citizens. The only exception is a recent contribution by Haugsgjerd (2019), who demonstrates that supporters of the Norwegian radical-right populist Fremskrittspartiet have expressed increasing satisfaction with democracy after the party had gained executive power in 2013. Adding to both of these literatures, this article wants to contribute to our understanding of what the new realities of populism mean for Europe's democracies by examining how the electoral success of populist parties affects political trust in the general public and whether and how this effect varies across countries depending on democratic quality, corruption control, and government performance.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the net effect seems positive because the nativists' reaction is stronger than non-nativists' reaction, however, provocatively points to the conclusion that general SWD will increase if established parties continue their inclusive strategies towards PRR parties, at least in the short term. This is also suggested by a recent study on the effects of the inclusion of the Norwegian Progress Party in government after the 2013 election (Haugsgjerd, 2019).…”
Section: Discussionmentioning
confidence: 53%
“…This could help explain why there has been an increase in aggregate satisfaction with the way democracy works in countries after established parties have invited PRR parties as coalition partners. Empirical evidence of such an inclusion effect is scarce, but in a recent study of Norway, Haugsgjerd (2019) found that the gap in political support between Progress Party voters and mainstream party voters narrowed over time after the Progress Party joined a coalition government in 2013. This, in turn, might explain why sustained populist success has not been accompanied by a drastic decrease in satisfaction with democracy across Europe.…”
Section: The Expected Effects Of Inclusion On Non-nativistsmentioning
confidence: 99%
See 1 more Smart Citation